Colored light-quality selective plastic films affect anthocyanin content, enzyme activities, and the expression of flavonoid genes in strawberry (Fragaria × ananassa) fruit. (15th September 2016) - Miao, Lixiang; Zhang, Yuchao; Yang, Xiaofang; Xiao, Jinping; Zhang, Huiqin; Zhang, Zuofa; Wang, Yuezhi; Jiang, Guihua
Highlights: Colored films were only used to cover developing strawberry fruits. Colored films had significant effect on anthocyanin metabolism in strawberry fruit. Treatment with red and yellow films can enhance the anthocyanin content in fruit. Abstract: The influence of colored light-quality selective plastic films (red, yellow, green, blue, and white) on the content of anthocyanin, the activities of the related enzymes and the transcripts of the flavonoid gene was studied in developing strawberry fruit. The results indicated that colored films had highly significant effects on the total anthocyanin content (TAC) and proportions of individual anthocyanins. Compared with the white control film, the red and yellow films led to the significant increase of TAC, while the green and blue films caused a decrease of TAC. Colored film treatments also significantly affected the related enzyme activity and the expression of structural genes and transcription factor genes, which suggested that the enhancement of TAC by the red and yellow films might have resulted from the activation of related enzymes and transcription factor genes in the flavonoid pathway. Treatment with red and yellow light-quality selective plastic films might be useful as a supplemental cultivation practice for enhancing the anthocyanin content in developing strawberry fruit.